Traditional and Modern Cuisine of the Inhabitants of the Former Sandomierz Primeval Forest in the Research of the Folk Culture Museum in Kolbuszowa - Lipelt, Robert (Literatura Ludowa. Journal of Folklore and Popular Culture, 2020)
Review: Puszcza Sandomierska od kuchni. Między tradycją a współczesnością, pod red. K. Smyk, T. Pudłockiego, I. Wodzińskiej, Muzeum Kultury Ludowej w Kolbuszowej, Kolbuszowa 2017.